Efektivitas Pemberian Jus Buah Nanas dan Madu Terhadap Proses Penyembuhan Luka Perineum Pada Ibu Post Partum - Lia Idealistiana; Andriani Utami (Universitas Pahlawan Tuanku Tambusai, 2025)
Perineal wounds are injuries that occur during childbirth in the perineum due to pressure from the baby's head at birth, there are most women who experience perineal rupture during childbirth, approximately 50-60% of these women require stitches. Healing of perineal wounds can be done using pharmacological and non-pharmacological therapy, mothers who choose non-pharmacology can be done at home easily and cheaply, one of which is by giving pineapple juice and honey. This type of research is a descriptive analytical pre-experimental study with a pretest posttest non-equivalent group design with a hypothesis test using the Wilcoxon approach. The sampling technique is Total sampling. The results of the study of Perineal Wounds of Postpartum Mothers Before and After Giving Pineapple Juice and Honey on day 1, the significance value is 1,000 (> 0.05) and on days 2 to 7 the significance value (<0.05). The value of Asym.sig 2 failed < 0.05 means there is an average difference from day 4 to day 7 with a significance value of less than 0.05.